Analisis Perbandingan Kinerja Keuangan Lembaga Amil Zakat Yayasan Amal Sosial Ash Shohwah Malang Sebelum dan Selama Pandemi Covid-19 - Imran, Nadya Tri Octaviani; Badriyah, Nurul (MES Management Journal, 2024)
This research aims to compare the financial performance of LAZ YASA Malang before and during the Covid-19 pandemic. The research method used is quantitative research with a comparative approach. The data obtained is secondary data consisting of the financial ratios of LAZ YASA Malang for the period 2018-2021. The results of the research show that there is no significant difference in the financial performance of LAZ YASA Malang before and during the Covid-19 pandemic. However, most of the financial ratios of LAZ YASA Malang have shown improvement and are considered good and efficient according to the interpretation of OPZ financial ratios. Ratios such as fundraising costs, current ratio, quick ratio, growth of zakat, growth of infaq, growth of ZIS, and growth of allocation indicate a decline in performance during the Covid-19 pandemic. This provides an opportunity for LAZ YASA Malang to evaluate and enhance their financial performance in managing and distributing zakat, infaq, and Shadaqah funds. This research contributes to the understanding of the financial performance of zakat amil institutions during the Covid-19 pandemic. The findings can be used as a reference for LAZ YASA Malang to optimize the management and distribution of zakat, infaq, and Shadaqah funds. Additionally, this research provides valuable information for further research and development in the field of financial performance of zakat amil institutions.